PERENCANAAN BANGUNAN PELINDUNG PANTAI PULAU NIPA PROVINSI KEPULAUAN RIAU - Nathaniel, Bagas
Indonesia is one of the largest archipelagic countries as well as the country with the longest coastline in the world, so Indonesia has great potential in its coastal and marine areas. However, behind the great potential, there is the threat of beach damage caused by natural phenomena such as sea waves, sea storms, tides, etc. as well as damage due to human activities such as dredging or mining of beach sand. This coastal damage can be a threat to Indonesian sovereignty. One of the coastal damage that occurred was on Nipa Island, a small island with an area of approximately 50 hectares located in the Riau Islands. This island is one of the outer islands of Indonesia or an island on the border between Indonesia and Singapore. Nipa Island has suffered damage due to coastal sand mining which has damaged the structure of this island, coupled with natural phenomena such as tides and sea waves that make Nipa Island sink. Therefore, a beach protection building is needed so that Nipa Island does not sink and becomes an effort to protect the sovereignty of the Republic of Indonesia. The safety / beach building designed for Nipa Island is a breakwater with waves and a design period of 2.9 meters and 8 seconds, respectively. With a breakwater design height of 9 meters, a lighthouse width of 3 meters, 1.5 meters thick primary layer armor, and 1 meter thick secondary layer armor. The material used for the armor is crushed stone with a specific gravity criteria of 2.65 tons / m3 with a stone weight for primary armor weighing 2 tons, for secondary armor weighing 200 kg, and for core layers weighing 20 kg. The total volume of buildings planned for the vicinity of Nipa Island is 728,816 m3 with a planned budget of Rp. 215,655,390,000, -